2001
DOI: 10.1038/labinvest.3780209
|View full text |Cite
|
Sign up to set email alerts
|

Cell Invasion Is Affected by Differential Expression of the Urokinase Plasminogen Activator/Urokinase Plasminogen Activator Receptor System in Muscle Satellite Cells from Normal and Dystrophic Patients

Abstract: SUMMARY:The aim of this study was to evaluate the differential expression and the function in cell movement and proliferation of the urokinase plasminogen activator (u-PA) system in muscle satellite cells (MSC) of normal individuals and patients with Duchenne muscular dystrophy (DMD). By immunoenzymatic, zymographic, and radioligand binding methods and by quantitative polymerase chain reaction of the specific mRNA we have shown that both normal and DMD MSC produce u-PA and the plasminogen activator inhibitor-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 33 publications
2
51
0
Order By: Relevance
“…Previous studies have demonstrated that antibodies against uPA or uPAR impaired satellite cell migration and fusion in vitro (5,12,15). In the present study, isolated satellite cells from WT and uPAR Ϫ/Ϫ neonatal mice were induced to fuse in differentiation medium for 72 h. The resulting myotubes were stained and the percentage of nuclei in myotubes with Ն3 nuclei were counted (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that antibodies against uPA or uPAR impaired satellite cell migration and fusion in vitro (5,12,15). In the present study, isolated satellite cells from WT and uPAR Ϫ/Ϫ neonatal mice were induced to fuse in differentiation medium for 72 h. The resulting myotubes were stained and the percentage of nuclei in myotubes with Ն3 nuclei were counted (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, treatment of monocytes with an anti-uPAR antibody suppressed chemotaxis induced by fMLP in vitro (19), and peritoneal macrophages collected from uPAR Ϫ/Ϫ mice failed to promote plasminogen activation (7). In vitro experiments with muscle satellite cells or myoblasts demonstrated that antibodies against uPA or uPAR impaired cell proliferation, migration, and fusion (5,12,15,31,47). uPAR may contribute to these processes through different mechanisms.…”
mentioning
confidence: 99%
“…Our data are consistent with prior reports in which uPA was shown to stimulate proliferation of human myoblasts in a dose-dependent manner. 26,39 Furthermore, a blocking antibody against uPA inhibited basic fibroblast growth factor-induced proliferation, indicating that uPA may mediate proliferation induced by fibroblast growth factor. 26,39 Studies on vascular smooth muscle cells produced similar findings that uPA induces proliferation of these cells and may mediate growth factor-induced proliferation.…”
Section: Org Frommentioning
confidence: 99%
“…26,39 Furthermore, a blocking antibody against uPA inhibited basic fibroblast growth factor-induced proliferation, indicating that uPA may mediate proliferation induced by fibroblast growth factor. 26,39 Studies on vascular smooth muscle cells produced similar findings that uPA induces proliferation of these cells and may mediate growth factor-induced proliferation. [40][41][42] Our data demonstrated that (1) intact uPA but not the aminoterminal fragment, which lacks the proteolytic domain, stimulated myoblast proliferation; (2) the specific proteolytic inhibitor PAI-1 blocked uPA-mediated myoblast proliferation; (3) the HGFblocking antibody reduced uPA stimulation of myoblast proliferation; and (4) both the PI3K inhibitor LY and the MEK1 inhibitor PD98059 reduced uPA-mediated myoblast proliferation.…”
Section: Org Frommentioning
confidence: 99%
“…14) A549 cells were plated at 5×10 5 cells/well in 6 well plates for 24 h. The cells were treated with various concentrations of shikonin and its derivatives for 24 h. Total RNA was prepared from A549 cells by using Trizol reagent. Total RNA (1.0 mg) was reverse transcribed by using oligo poly (dT) and MMLV reverse transcriptase.…”
Section: Measurement Of Hvegfmentioning
confidence: 99%